A COVID in the wheels of the world: A contemporary history of a pandemic in Africa. (December 2021) - Adu-Gyamfi, Samuel; Brenya, Edward; Gyasi, Razak M.; Abass, Kabila; Darkwa, Benjamin Dompreh; Nimoh, Michael; Tomdi, Lucky
Abstract: Several pandemics have been reported throughout history. The Black Death, Spanish flu, Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) among many others have received attention by both earlier and recent scholarships due to their impact on humanity. Before the outbreak of COVID-19, scholars had anticipated future outbreaks with the same or greater impact. The coronavirus which spread from Wuhan from December 2019, across nations has already decimated over 2 million lives with the Americans and Europeans scoring higher in mortality rates. Since its outbreak, scholars have reported cases and measured its impact concerning nations and the international economy. From a historical political economy approach, we add to the corpus of information on pandemics by using the theories of globalizations to discuss pandemics and COVID-19 in particular. We have highlighted the economic history of earlier pandemics and related same to the current burden. We discuss how resources have been distributed to address health systems of Africa and Ghana in particular. Also, the current contribution pays attention to critical questions on COVID-19 in Africa. Evidence from the study suggests that African nations shall do better when they combine their efforts and resources to fight the pandemic and others that might erupt in the near future. From the discussions, we draw lessons for stakeholders and policy makers.